2013
DOI: 10.1111/ijn.12128
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aromatherapy and massage administered in different ways to women with breast cancer on their symptoms and quality of life

Abstract: The primary objective of this study was to assess the effect of aromatherapy and classic massage administered in various ways to breast cancer patients on their symptoms and quality of life. The sampling consisted of 280 patients. Quality of life and symptoms of the patients were evaluated once at baseline and then at week 6 and week 10 following the intervention. After intervention, the control group was observed to have lower total quality of life score and subdomain scores, whereas fragrance, massage and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 28 publications
(80 reference statements)
1
19
0
30
Order By: Relevance
“…The difficulty of screening cancer patients regarding psychosocial intervention is well known [51,52]. Since the effectiveness of massages, yoga, and psychological assistance in promoting mental health has been assessed [23,24,25,53,54], modern oncology should implement such interventions in order to ensure the highest possible psychological well-being among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of screening cancer patients regarding psychosocial intervention is well known [51,52]. Since the effectiveness of massages, yoga, and psychological assistance in promoting mental health has been assessed [23,24,25,53,54], modern oncology should implement such interventions in order to ensure the highest possible psychological well-being among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies (Bishop, Yardley, & Lewith, ; Nelson, ), this study indicated that ATM was viewed by patients with cancer as a “treat” rather than a “treatment.” Moreover, the participants valued the therapy as beneficial to them in the cancer journey. Different studies that assessed the effect of massage with or without aromatherapy on Western cancer patients described such therapy as a buffer against tension and uneasiness, balancing negative feelings of cancer treatments and prognosis with positive feelings of ATM (Billhult, Stener‐Victorin, & Bergbom, ; Dunwoody et al., ; Ovayolu, Sevig, Ovayolu, & Sevinc, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, breast cancer women in our study presented with positive experiences in relation to body image. While existing literature has well described that ATM showed benefits for reducing physical discomfort and mood disturbances in breast cancer patients (Imanishi et al., ; Ovayolu et al., ), its potential benefits for enhancing one's perceived body image have not been widely covered. Previous work by Billhult et al.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini didukung oleh penelitian sebelumnya bahwa episode nausea dan vomiting pada ibu hamil menurun pada hari ketiga pasca inhalasi aromaterapi (Mahmoud, Ghani, Tawfik, & Ibrahim, 2013). Atau hasil penelitian yang dilakukan oleh Ovayolu, Sevið, Ovayolu, & Sevinç, (2014) tentang efektivitas aromaterapi terhadap breast cancer symptom dan kualitas hidup pasien kanker payudara. hasil penelitian tersebut menunjukkan terdapat penurunan Symptom fisik dan peningkatan kualitas hidup pasien kanker payudara dari minggu ke-6 hingga minggu ke-10 pada kelompok intervensi Lavender memiliki sejarah panjang sebagai anticonvulsant,antidepressive, anxiolytic, sedative, and penenang.…”
Section: Pembahasanunclassified